Risk model for severe postoperative complications after total pancreatectomy based on a nationwide clinical database. Issue 6 (31st January 2020) - Hashimoto, D.; Mizuma, M.; Kumamaru, H.; Miyata, H.; Chikamoto, A.; Igarashi, H.; Itoi, T.; Egawa, S.; Kodama, Y.; Satoi, S.; Hamada, S.; Mizumoto, K.; et al.
Abstract : Background: Total pancreatectomy is required to completely clear tumours that are locally advanced or located in the centre of the pancreas. However, reports describing clinical outcomes after total pancreatectomy are rare. The aim of this retrospective observational study was to assess clinical outcomes following total pancreatectomy using a nationwide registry and to create a risk model for severe postoperative complications. Methods: Patients who underwent total pancreatectomy from 2013 to 2017, and who were recorded in the Japan Society of Gastroenterological Surgery and Japanese Society of Hepato‐Biliary‐Pancreatic Surgery database, were included. Severe complications at 30 days were defined as those with a Clavien–Dindo grade III needing reoperation, or grade IV–V. Occurrence of severe complications was modelled using data from patients treated from 2013 to 2016, and the accuracy of the model tested among patients from 2017 using c‐statistics and a calibration plot. Results: A total of 2167 patients undergoing total pancreatectomy were included. Postoperative 30‐day and in‐hospital mortality rates were 1·0 per cent (22 of 2167 patients) and 2·7 per cent (58 of 167) respectively, and severe complications developed in 6·0 per cent (131 of 2167). Factors showing a strong positive association with outcome in this risk model were the ASA performance status grade and combined arterial resection. In the test cohort, the c‐statistic of the model was 0·70 (95 per cent c.i. 0·59 to 0·81). Conclusion: The risk model may be used to predict severe complications after total pancreatectomy. Abstract : This study assessed the clinical outcomes of total pancreatectomy using a nationwide registry in Japan, and proposed a risk model for severe postoperative complications. Rates of mortality and severe complication after total pancreatectomy were lower in this study than in previous reports. The risk model showed good calibration. Tool for preoperative risk estimation Abstract : Antecedentes: La pancreatectomía total está indicada cuando se requiere la resección completa de tumores localmente avanzados o ubicados en el centro del páncreas. Sin embargo, existen pocos artículos que describan los resultados clínicos después de una pancreatectomía total. El objetivo de este estudio observacional retrospectivo fue evaluar los resultados clínicos después de una pancreatectomía total utilizando un registro nacional y crear un modelo de riesgo de complicaciones postoperatorias graves. Métodos: Se incluyeron aquellos pacientes que se sometieron a una pancreatectomía total entre 2013 y 2017 y que fueron registrados en la base de datos de la Sociedad Japonesa de Cirugía Gastrointestinal y de la Sociedad Japonesa de Cirugía Hepato‐Bilio‐Pancreática. Las complicaciones graves a los 30 días se definieron como Clavien‐Dindo grado III con reintervención o grado IV/V. Se analizó la aparición de complicaciones graves de los pacientes desde 2013 a 2016 y se evaluó la precisión del modelo entre los pacientes operados desde 2017 usando estadísticos c y un gráfico de calibración. Resultados: Se incluyeron 2.167 pacientes sometidos a una pancreatectomía total. La mortalidad postoperatoria a los 30 días y la mortalidad hospitalaria fueron del 1, 0% (22/2167) y del 2, 7% (58/2167), respectivamente, y las complicaciones graves ocurrieron en el 6, 0% (131/2167) de los pacientes. Los factores que mostraron una fuerte asociación positiva con los resultados en este modelo de riesgo fueron el estado funcional según la Sociedad Americana de Anestesiología y la resección arterial combinada. En la cohorte de prueba, el estadístico c del modelo fue de 0, 70 (i.c. del 95% 0, 59‐0, 81). Conclusión: El modelo de riesgo puede usarse para predecir las complicaciones graves después de una pancreatectomía total.